Safety and Efficacy: Clinical Experience of Venetoclax in Combination With Hypomethylating Agents in Both Newly Diagnosed and Relapsed/Refractory Advanced Myeloid Malignancies. Issue 4 (9th April 2021) - Feld, Jonathan; Tremblay, Douglas; Dougherty, Mikaela; Czaplinska, Tina; Sanchez, Gillian; Brady, Claudia; Kremyanskaya, Marina; Bar-Natan, Michal; Keyzner, Alla; Marcellino, Bridget K.; Gabrilove, Janice; Navada, Shyamala C.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Hypomethylating agents (HMAs) in combination with venetoclax have been widely adopted as the standard of care for patients who cannot tolerate induction chemotherapy and for patients who have relapsed/refractory (R/R) acute myeloid leukemia (AML). This study retrospectively analyzed the outcomes of all patients with AML (n = 65) or myelodysplastic syndrome (n = 7) who received the combination of HMA and venetoclax at our institution. Outcomes measured included complete remission (CR) and CR with incomplete hematologic recovery (CRi) rates, duration of response (DOR), and overall survival (OS). Patient mutational profiles and transfusion requirements were also assessed. Of 26 newly diagnosed AML patients, the CR/CRi rate was 53.8%. The median DOR and OS were 6.9 months and not reached, respectively. Of 39 R/R AML patients, the CR/CRi rate was 38.5%. The median DOR and OS were both 8.1 months. Responders to HMA and venetoclax were enriched for TET2, IDH1, and IDH2 mutations, while nonresponders were associated with FLT3 and RAS mutations. Adaptive resistance was observed through various mechanisms including acquired RAS pathway mutations. Of transfusion-dependent patients, 12.2% and 15.2% achieved red blood cell (RBC) and platelet transfusion independence, respectively, while 44.8% and 35.1% of RBC and platelet transfusion independent patients, respectively, became transfusion dependent. In total 59.1% of patients developed a ≥grade 3 infection and 46.5% neutropenic fever. HMA + venetoclax can lead to impressive response rates with moderately durable remissions and survival. However, the benefits of this combination are diminished by the significant toxicities from infection, persistent cytopenias, and transfusion requirements.